1993
DOI: 10.1046/j.1365-2648.1993.18030387.x
|View full text |Cite
|
Sign up to set email alerts
|

Intuition as a function of the expert nurse: a critique of Benner's novice to expert model

Abstract: Benner's model of skill acquisition is currently receiving considerable interest from nurse educationalists, and promises to form the basis for some curricula offered by colleagues of nurse education. This paper debates the 'novice to expert' model and seeks to explain exactly what an 'expert' is. The Benner model proposes that one component of expertise is working from an intuitive base. This claim is disputed and the definition of intuition is contested. Alternative explanations to account for the intuitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
102
1
7

Year Published

1994
1994
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(111 citation statements)
references
References 11 publications
1
102
1
7
Order By: Relevance
“…Despite the age of this literature, the work and the generalisability of the findings owing to the study carried out in a different cultural setting (Gately, 1992), Benner had been instrumental in examining skill acquisition in nursing "from novice to expert" and has been referred to in abundant literature worldwide (Silver, 1986;English, 1993).…”
Section: Sources Of Stressmentioning
confidence: 99%
“…Despite the age of this literature, the work and the generalisability of the findings owing to the study carried out in a different cultural setting (Gately, 1992), Benner had been instrumental in examining skill acquisition in nursing "from novice to expert" and has been referred to in abundant literature worldwide (Silver, 1986;English, 1993).…”
Section: Sources Of Stressmentioning
confidence: 99%
“…The role of intuition in nursing has been the topic of considerable debate, with some authors (such as English, 1993) considering that this concept should be subjected to critical scrutiny at best and rejected at worst, while others (such as Darbyshire, 1994;Effken, 2001;King & Appleton, 1997) considering it central to our understanding of nursing expertise. In particular, the work of Patricia Benner and her colleagues (Benner, 1984;Benner et al, 1992;Benner, Tanner, & Chesla, 1996) has done much to convince the field of nursing of the importance of intuition.…”
Section: Intuition In Nursing Practicementioning
confidence: 99%
“…From an educational point of view, the emphasis on learning in context counterbalances the habitual focus on theoretical instruction (English, 1993). Finally, it is worth mentioning that Benner (1984), while mostly using interpretive phenomenology as her main tool, also refers to objective measures such as patient outcome.…”
Section: Strengths Of the Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…This clinician and patient relationship has been described as intuitive practice (English 1993;Gore & Sadler-Smith 2011;Smith et al 2004) and is well documented in nursing literature. A qualitative study that explored the opinions and beliefs of nurses' intuition, suggested that it is an interaction of attributes including: expertise; knowledge; personality; and the environment (McCutcheon and Pincombe 2001).…”
Section: Cognition and Emotional Markersmentioning
confidence: 95%